Models for Quantifying Winter Effective Chilling Adapted to Uruguayan Apple Production - Severino, Vivian; Arbiza, Héctor; Arias, Mercedes; Manzi, Matías; Gravina, Alfredo (Agrociencia Uruguay, 2011)
In Uruguay UTAH and CH models are usually applied for estimation of chilling accumulation, regardless of which specie or cultivar is considered, although there are evidences of lack of fitness to the phenologyc behaviour of the most cultivars. Chemical rest breaking agents to compensate the chilling requirements in apple (Malus domestica Borkh) are widely used and winter chill quantification should be a relevant issue to adjust this technique. The objective of this work was to quantify the occurrence of winter chill during the endodormancy period with six models, in two apple cultivars (‘Red Chief’, ‘Granny Smith’), according to development indicators of sprouting process. The models used were CH, UTAH, UTAH+, Dynamic Model, North Carolina Model and Model for Subtropical Conditions. Beginning of the endodormancy release was considered when 50% of leaf fall was reached and the end of the process when 50% of one-year-old shoot buds sprouted in a forcing chamber. Although the Dynamic model appears to be more promising, a longer evaluating period is needed to evaluate the fitness of these models.